Recent advances on algorithms and applications of soil moisture retrieval from microwave remote sensing - DENG Xiaodong; WANG Hongquan (浙江大学学报. 农业与生命科学版, 2022)
Soil moisture is a sensitive factor for crop phenological growth, climate and environment changes, and it plays an important role in the land surface water and atmospheric circulation. In this paper, the soil moisture retrieval algorithms based on active microwave remote sensing, passive microwave remote sensing and Global Navigation Satellite System Reflectometry (GNSS-R) technology were firstly sorted, including: 1) active microwave remote sensing-based empirical model, semiempirical model, physical scattering model for bare ground surface, and water cloud model (WCM), Michigan microwave canopy scattering (MIMICS) model for vegetation coverage; 2) passive microwave remote sensing-based Q/H, Hp, Qp roughness models for bare ground surface and <alternatives>τ<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/AD9F0769-7DD8-4be5-A9F4-CFE4CFB7E8CA-M003.jpg"/></alternatives>-<alternatives>ω<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/AD9F0769-7DD8-4be5-A9F4-CFE4CFB7E8CA-M004.jpg"/></alternatives> model for vegetation coverage; 3) spaceborne and ground-based GNSS-R soil moisture retrieval algorithms. Secondly, the research and development of soil moisture retrieval from microwave remote sensing in recent decades were reviewed. It was proposed that the key to improve the accuracy of soil moisture retrieval was to quantify accurately the spatial and temporal variability of soil moisture retrieval factors such as vegetation and surface roughness, especially the uncertainty of vegetation growth process and the resulting electromagnetic wave radiation transmission mechanism. Finally, the application outlook of soil moisture in agricultural production and land-surface moisture circulation was prospected, and it was pointed out that the response and feedback mechanism of soil moisture on global scale to climate change would be a research hotspot in the future.